Predictors of Mortality in Paraquat Poisoning: A Two-Year Retrospective Analysis From A Tertiary Care Teaching Hospital in South India - William Wilson; Rachana Bhat; Bharath Angadi; Nymisha Lekha; Bhavya Balaji; Jayaraj Mymbilly Balakrishnan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Backgrounds: Paraquat is a major cause of fatal poisoning in agro-based countries like India. Being, aveiled offender it is often deluded for its relatively less fatal counterpart i.eorganophhosporous compounds.It is a highly lethal herbicide, contributing to a majority of the pesticide poisoning related deaths & DisabilityAdjusted Life Years (DALY) globally.Methods: A retrospective record review of the patients presenting with paraquat poisoning to the EmergencyMedicine Department of a tertiary care center in South India,between August 2014 to August 2016 was done.Demographics, clinical presentation, and laboratory data of patients were analysed to study risk factorsassociated with morbidity & mortality.Results: 91 case were evaluated, of which 65.9% were male and majority (78.1%) belonged to the age group20-30 years and 31 (34%) being agriculturists. 85 (93.4%) attempts were suicidal in nature. Most commonpresenting symptom was vomiting 72 (79.1%), 27% of the patients had hypoxia (pao2<70%) however theinitial mean circulatory assessment were within stable limits (HR- 84/min, BP- 124/78mmhg). Investigationsrevealed average serum creatinine of 2.8mg/dL (+ 3.16) and bicarbonate of 17.6 mg/dL (+ 4.47). Treatmentmeasures included gastric lavage (67%) and haemoperfusion (49.5%) amongst others.47 (51.6%) patientsdied with the most common cause of death being Multiorgan dysfunction syndrome -MODS (61.7%) andAcute Kidney Injury-AKI (29.7%).To determine predictors of mortality, univariate and multivariate analysis[adjusted odds ratio (95% confidence intervals)] was done which revealed low bicarbonate6.174[1.20-31.59]and hypokalemia4.79 [1.08-21.19] to be significant risk factors.Conclusion: Paraquat poisoning has a high disease burden and concerning mortality ratesespecially inyoung and middle aged adults.Risk factors for mortality include low bicarbonate, hypokalemia and increasedserum creatinine with AKI and MODS being the most common causes of death.